Afirmasi Budaya Anti Bullying Terhadap Anak Didik Melalui Layanan Konseling Kelompok - S Suroso (BUANA GENDER : Jurnal Studi Gender dan Anak, 2018)
This study attempts to describe the efforts of anty bullying become mainstream in school. Bullying means any forced process happened by some students to other students or from the teahcer into students, bullying in question is any forcing process that often happens done by fellow peers (bullying) or from teachers to students in the form of violence symbol, physical, and verbal. This study uses a literature study method that attempts to formulate the role of Guidance and Counseling institutions in guarding and fostering nonviolent movements in schools, and learning models that can prevent the occurrence of violence in schools. So, the practice of violence in school can be minimized and even eliminated. In this study, it was concluded that the implementation of group counseling in anti-bullying campaigns could be possible as an alternative way to reduce bullying behavior in schools.